An Analysis of Translation Error that Occurs among English Foreign Language Students - Siti Magfiroh; Kheryadi (Stairs, 2021)
The quality of translation can affect the quality of information conveyed. However, errors often occur. It is evidenced by the various errors that can be found in this study. The objectives of this study are: 1) To check types of translation errors in Indonesian to English translation. 2) To find the possible explanations for the sources of errors made by the students in translation. The researcher hopes that it can help students to enrich their knowledge about learning translation. The methodology of this study was qualitative in case study design. The data was obtained from student tests. Researchers also conducted interviews to find out the source of the translation error. It analyzed the data and calculated each error with frequency and percentage. The respondents of this study were English Foreign Language students of Class TBI-E 2016 of UIN SMH Banten. They made some errors when they translated text from Indonesian into English. The researcher found that each error was a syntax error (68.13%), then a semantic error (31.87%). Researchers also found sources of translation errors: lack of linguistic understanding, translation procedures, unconfident, and inattention. The recommendation from the researcher is to inform students about the correct translation procedure. Moreover, more tasks about vocabulary and structure hope to be able to increase their English skill